Iowa Birdline update, January 7, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of the Iowa Birdline update for January 7, 1991. Highlights include a Yellow Grosbeak and numerous flocks of Lapland Longspurs and Snow Buntings. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed